Problem-Based Learning Model Using Oodlu Digital Media On Learning Outcomes - Sulistiyawati, Erani; Rusnilawati, Rusnilawati (Universitas Pakuan, 2024)
This study aims to evaluate the effectiveness of using problem-based learning with Oodlu tools in enhancing the learning of IV students in natural sciences (science and general studies). A quantitative and qualitative approach is used in this research. A learning-based model is used in three learning sessions using Oodlu media to enhance student engagement and enhance learning. A comparative study was conducted with students from the study group (N=15) who received the Oodlu media-based problem-based learning model and the control group (N=15) who received the corresponding learning model. Data analysis showed significant differences in learning outcomes between the two groups. Significant improvements in learning outcomes were demonstrated for science students participating in the problem-based learning model and Audlemedia. The integration ofProblem-Based Learning with Oodlu media has been proven to be effective in improving the intermediate learning outcomes (N-gain test). This confirms This means that the implementation of problem-based learning has a significant impact on the quality of learning of school children.